2017
DOI: 10.1039/c6ra26614b
|View full text |Cite
|
Sign up to set email alerts
|

Selenium supplementation can protect from enhanced risk of keel bone damage in laying hens exposed to cadmium

Abstract: The aim of this study was to investigate whether selenium (Se) supplementation can provide protection from an enhanced risk of keel bone damage (KBD) in laying hens due to the cadmium (Cd) toxicity associated with sub-chronic exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In a study by Imafidon et al [7], treating rats with cadmium nephropathy with an extract from Vernonia amygdalina , a plant rich in antioxidant polyphenols, restored the proper functioning of kidneys, normalized urea and creatinine levels, increased the concentration of reduced glutathione, and decreased the level of malonylodialdehyde. Administration of selenium to layer hens decreased cadmium concentration in bones, stimulated the bone formation processes, and inhibited bone resorption [8]. In rats, intraperitoneal administration of strawberry ( Fragaria ananassa ) extract, containing flavonoids and polyphenols of antioxidant, anti-apoptotic, anti-inflammatory, and chelating impact, alleviated neurotoxic effects of cadmium, decreased Cd concentration in the brain, and reduced lipid peroxides level and the expression of proinflammatory cytokine TNF-α (tumor necrosis factor α) protein.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Imafidon et al [7], treating rats with cadmium nephropathy with an extract from Vernonia amygdalina , a plant rich in antioxidant polyphenols, restored the proper functioning of kidneys, normalized urea and creatinine levels, increased the concentration of reduced glutathione, and decreased the level of malonylodialdehyde. Administration of selenium to layer hens decreased cadmium concentration in bones, stimulated the bone formation processes, and inhibited bone resorption [8]. In rats, intraperitoneal administration of strawberry ( Fragaria ananassa ) extract, containing flavonoids and polyphenols of antioxidant, anti-apoptotic, anti-inflammatory, and chelating impact, alleviated neurotoxic effects of cadmium, decreased Cd concentration in the brain, and reduced lipid peroxides level and the expression of proinflammatory cytokine TNF-α (tumor necrosis factor α) protein.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Waeli et al (37) also reported that Se at 3 mg/kg has no significant influence on the Cd deposition in the kidney and liver of broilers when 100 mg Cd /kg was supplemented with the diet. In contrast, Zhang et al (14,38,39) found that Se at 2 mg/kg ameliorated deposition of Cd in the kidneys, liver and bone of laying hens by dietary addition of 150 mg /kg Cd. The discrepancies in these findings might be due to the differences in the selected tissues, the mineral dosages, Se form, and poultry species.…”
Section: Discussionmentioning
confidence: 89%
“…Se is a micro-element involved in mitigating the effects of oxidative stress and improving bone health by reducing bone resorption. Previous studies indicated that Se supplementation reduced the Cd-induced risk of KBD in laying hens ( 32 ). From above discussed results, it can be hypothesized that an increased Se content as a result of SO supplementation may have played a protective role against KBD induced by high levels of Mn and Fe in laying hens.…”
Section: Discussionmentioning
confidence: 97%